ANALISIS TEMPAT, LAYANAN, KREATIFITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI MASKET PLACE - Herawati, Yeni; Nasution, Meisa Fitri; Gulo, Nur’Ainun (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research aims to analyze the influence of place, service, product creativity and promotion factors on purchasing decisions in the marketplace. Marketplaces as electronic trading platforms have become the main choice for many consumers in making purchases. Place factors, the services provided, the creativity of the products offered, as well as the promotional strategies implemented, play a major role in influencing consumer purchasing decisions. The research method used is a quantitative approach by collecting data through questionnaires distributed to marketplace users in Teluk Panji Village. The data obtained was then analyzed using multiple linear regression techniques to find out how much influence each independent variable had on purchasing decisions. The research results show that all independent variables, namely place, service, product creativity and promotion, have a positive and significant influence on purchasing decisions. The product creativity variable has the most dominant influence, followed by service, place and promotion. These findings indicate that to improve purchasing decisions, marketplaces need to pay more attention to increasing innovation in product creativity, better service, more strategic locations and effective promotions. This research provides practical contributions for marketplace managers in designing better marketing strategies and provides insight for future researchers to develop studies related to other variables that may influence purchasing decisions in the marketplace.